Identifying common pathways for doxorubicin and carfilzomib-induced cardiotoxicities: transcriptomic and epigenetic profiling - Conagh Kelly; Dylan J. Kiltschewskij; Angeline J.W. Leong; Tatt Jhong Haw; Amanda J. Croft; Lohis Balachandran; Dongqing Chen; Danielle R. Bond; Heather J. Lee; Murray J. Cairns; Aaron L. Sverdlov; Doan T. M. Ngo (Scientific Reports)
Abstract Cancer therapy-related cardiovascular toxicity (CTR-CVT) is now recognised as one of the leading causes of long-term morbidity and mortality in cancer patients. To date, potential overlapping cardiotoxicity mechanism(s) across different chemotherapeutic classes have not been elucidated. Doxorubicin, an anthracycline, and Carfilzomib, a proteasome inhibitor, are both known to cause heart failure in some patients. Given this common cardiotoxic effect of these chemotherapies, we aimed to investigate differential and common mechanism(s) associated with Doxorubicin and Carfilzomib-induced cardiac dysfunction. Primary human cardiomyocyte-like cells (HCM-ls) were treated with 1 µM of either Doxorubicin or Carfilzomib for 72 h. Both Doxorubicin and Carfilzomib induced a significant reduction in HCM cell viability and cell damage. DNA methylation analysis performed using MethylationEPIC array showed distinct and common changes induced by Doxorubicin and Carfilzomib (10,270 or approximately 12.9% of the DMPs for either treatment overlapped). RNA-seq analyses identified 5,643 differentially expressed genes (DEGs) that were commonly dysregulated for both treatments. Pathway analysis revealed that the PI3K-Akt signalling pathway was the most significantly enriched pathway with common DEGs, shared between Doxorubicin and Carfilzomib. We identified that there are shared cardiotoxicity mechanisms for Doxorubicin and Carfilzomib pathways that can be potential therapeutic targets for treatments across 2 classes of anti-cancer agents.